Respostas

A melhor resposta!
2013-11-20T01:00:16-02:00
4 (x + 2y) = 7 (2x + y) + 5
3x - 5y + 11 = 4 ( 5x - 2y)

4x + 8y = 14x + 7y + 5
3x - 5y + 11 = 20x - 8y

4x - 14x + 8y - 7y = 5
3x - 20x - 5y + 8y = - 11

- 10x + y = 5          (1)
- 17x + 3y = - 11     (2)
Agora, vamos usar o método de substituição:
y = 5 + 10x
Substituindo y em (2):
- 17x + 3 (5 + 10x) = - 11
- 17x + 15 + 30x = - 11
- 17x + 30x = - 11 - 15
13x = - 26
x = - 26 : 13
x = - 2

Então:
y = 5 + 10 x
y = 5 + 10 (- 2)
y = 5 - 20
y -= - 15

Resposta: x = - 2          y = - 15
3 5 3